2022
DOI: 10.3390/jcm11154264
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Observational Study of the Relationship between Outdoor Exposure and Myopia in University Students, Measured by Conjunctival Ultraviolet Autofluorescence (CUVAF)

Abstract: Myopia is the most common refractive error worldwide. This cannot be explained by genetic factors alone, therefore, environmental factors may play an important role. Hence, the main objective of this study was to analyse whether outdoor exposure could exert a protective effect against the development of myopia in a cohort of young adults and to investigate ultraviolet autofluorescence (CUVAF), as a biomarker of time spent outdoors. A cross-sectional observational study was carried out using two cohorts. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 41 publications
(68 reference statements)
2
11
0
Order By: Relevance
“…34,35 The efficacy rate of these interventions at preventing myopia within 1 year ranged from 11.0% to 54.3%. [11][12][13][14][15][16][17][18][19][20][21][22] Repeated low-level red-light (RLRL) therapy delivered by a device emitting 650-nm visible red light has been proposed as an alternative myopia control intervention. [36][37][38][39][40][41] Recent research has reported increased blood flow and stabilization of axial elongation among children after the RLRL intervention, which might suggest that RLRL therapy could ameliorate scleral hypoxia and thus prevent the development of myopia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…34,35 The efficacy rate of these interventions at preventing myopia within 1 year ranged from 11.0% to 54.3%. [11][12][13][14][15][16][17][18][19][20][21][22] Repeated low-level red-light (RLRL) therapy delivered by a device emitting 650-nm visible red light has been proposed as an alternative myopia control intervention. [36][37][38][39][40][41] Recent research has reported increased blood flow and stabilization of axial elongation among children after the RLRL intervention, which might suggest that RLRL therapy could ameliorate scleral hypoxia and thus prevent the development of myopia.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several interventions have been proposed to prevent the onset of myopia, such as increased outdoor time, 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 reducing activities done at a short working distance, 18 , 19 , 20 , 23 , 24 , 25 , 26 , 27 , 28 Chinese eye exercises, 29 , 30 , 31 , 32 , 33 and low-dose atropine. 34 , 35 The efficacy rate of these interventions at preventing myopia within 1 year ranged from 11.0% to 54.3%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies obtained the CUVAF measurement by custom-made photographic systems 22,[30][31][32][36][37][38][39] and one study using the Heidelberg OCT system. 29 All studies report that myopes have signi cantly smaller CUVAF areas than non-myopes.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Since it was rst described, different research groups have studied CUVAF area as a biomarker of sun exposure, moreover, recent publications have shown an inverse relationship between CUVAF area and myopia. 22,[29][30][31][32] Therefore it promises to be an inexpensive, reproducible, quick and easy method to use in a routine ophthalmology and optometry practice unlike other tests. However, these studies included very heterogeneous populations in terms of age and geographic location, which could in uence CUVAF area.…”
Section: 28mentioning
confidence: 99%